Diagonal movement of the upper limb produces greater adaptive plasticity than sagittal plane flexion in the shoulder. (16th March 2017) - Moreira, Rayele; Lial, Lysnara; Teles Monteiro, Maria Gabriela; Aragão, Alice; Santos David, Lorena; Coertjens, Marcelo; Silva-Júnior, Fernando L.; Dias, Gildário; Velasques, Bruna; Ribeiro, Pedro; Teixeira, Silmar Silva; Bastos, Victor Hugo
Highlights: The effects of PNF on the brain's electrical activity. PNF generates greater changes in cortical activity, as assessed by beta band absolute power levels. PNF generates greater neural recruitment for the execution of maneuvers, when compared with shoulder flexion in the sagittal plane alone. Abstract: The motor rehabilitation is based on exercises that involve various joints and muscle groups. One such treatment method is Proprioceptive Neuromuscular Facilitation (PNF), which involves diagonal movements simulating many activities of daily living. The objective of this study was to investigate the differences between PNF and shoulder flexion movements performed without the diagonal component (i.e., only in the sagittal plane) using beta band absolute power as a measure of plasticity. The study included 30 volunteers randomized into three groups (control, PNF, and FLEX), with electroencephalographic signals captured before and after the performance of the task. The PNF group showed an increase in beta band absolute power in both hemispheres, indicating greater plasticity than that seen in the FLEX group. Therefore, PNF seems to be capable of promoting cortical adaptations that lead to the recruitment of both hemispheres, thus influencing cortical organization in more complex tasks.